Forging Business-Labour Partnerships : The Emergence of Sector Councils in Canada - Sharpe, Andrew; Gunderson, Morley, 1945- (Book collections on Project MUSE., 1998)
This collection brings together the views of economists, political scientists, and industrial-relations specialists on a major innovation in Canadian industiral relations: joint business-labour sector councils.